1958
DOI: 10.1136/adc.33.171.455
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Dental Caries in Relation to Maturity

Abstract: This study constitutes part of an investigation of the epidemiology of dental caries in 4,034Edinburgh children in the age range 5-17 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

1965
1965
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 10 publications
0
0
1
Order By: Relevance
“…When comparing DMFT scores between male and female patients, the current study found no difference in contrast with the findings in studies by Lukacs, Mansbridge, and Cahen et al, who found that women had significantly higher DMFT scores than men in a healthy population ( Mansbridge, 1958 , Cahen et al, 1977 , Lukacs and Largaespada, 2006 , Lukacs, 2011a , Lukacs, 2011b ).…”
Section: Discussioncontrasting
confidence: 99%
“…When comparing DMFT scores between male and female patients, the current study found no difference in contrast with the findings in studies by Lukacs, Mansbridge, and Cahen et al, who found that women had significantly higher DMFT scores than men in a healthy population ( Mansbridge, 1958 , Cahen et al, 1977 , Lukacs and Largaespada, 2006 , Lukacs, 2011a , Lukacs, 2011b ).…”
Section: Discussioncontrasting
confidence: 99%